CREATION OF ASSESSMENT INSTRUMENTS IN DIFFERENTIAL LEARNING SYSTEMS (ATIKANOTO: Journal of Automotive Engineering Education, 2024)
The purpose of this study is to make an assessment that will be made in the form of an instrument performance assessment and multiple choice assessment instrument assessment with differential system material, by conducting a validation test on expert lecturers and vocational high school teachers. The type of method taken in this study is the Research and Development method with the 4D model, a research method used to produce products and test the effectiveness of the product. The population taken in this study were 30 students of class XI Automotive Light Vehicle Engineering (TKRO) with a purposive sampling technique. The preparation of this assessment instrument was validated by experts who were 2 expert lecturers and 3 teachers of the Automotive Light Vehicle Engineering Vocational High School. The testing carried out was in the form of a validity test using the Content Validity Ratio (CVR) and Content Validity Index (CVI) formulas and cognitive assessments using the Anatest program. Obtaining CVR results on 20 items of differential system practice activities were declared valid and 2 items of activities were declared invalid, while for the CVI results in this study, the value was 0.92 which was declared "special" and the results of the cognitive test validation showed that 18 items out of 20 questions were worthy of being used as a test tool and obtained a reliability value of 0.70 which was declared worthy of being used in differential system learning. Tujuan dari penelitian ini membuat penilaian yang akan dibuat adalah berbentuk asesmen instrumen kinerja dan asesmen instrumen penilaian pilihan ganda dengan materi sistem differential, dengan melakukan uji validasi pada dosen ahli dan guru SMK. Jenis metode yang diambil pada penelitian ini yaitu metode penelitian dan pengembangan Research and Development dengan model 4D suatu metode penelitian yang digunakan untuk menghasilkan produk, dan menguji keefektifan produk tersebut. Populasi yang diambil pada penelitian ini peserta didik kelas XI Teknik Kendaraan Ringan Otomotif (TKRO) berjumlah 30 peserta didik dengan teknik purposive sampling. Penyusunan instrumen asesmen ini divalidasi oleh para ahli yang merupakan 2 dosen ahli dan 3 guru SMK jurusan Teknik Kendaraan Ringan Otomotif. Pengujian dilakukan berupa uji validitas isi memakai rumus Content Validity Rasio (CVR) dan Content Validty Index (CVI) dan asesmen kognitif menggunakan program Anatest. Mendapatkan hasil CVR pada 20 butir kegiatan praktik sistem differential dinyatakan valid dan 2 butir kegiatan dinyatakan tidak valid, sementara untuk hasil CVI pada penelitian ini mendapatkan nilai 0,92 yang dinyatakan “istimewa” serta hasil validasi tes kognitif hasilnya 18 butir dari 20 butir soal layak dijadikan alat tes dan mendapatkan nilai reliabilitas 0,70 yang dinyatakan layak digunakan pada pembelajaran sistem differential.